2014
DOI: 10.3109/1354750x.2013.870605
|View full text |Cite
|
Sign up to set email alerts
|

Transcoronary gradient of plasma microRNA 423-5p in heart failure: evidence of altered myocardial expression

Abstract: The difference in transcoronary gradients between HF outpatients and controls suggests that miR-423-5p has a cardiac origin. The positive correlation between miR-423-5p and BNP transcoronary gradients supports this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 27 publications
1
55
2
1
Order By: Relevance
“…Besides these roles, miR-26a is also generally thought to be a tumor suppressor (Chen et al ., 2011; Reuland et al ., 2012; Salvatori et al ., 2012; Yang et al ., 2013). The expression of circulating miR-423 is related to myocardial function (Goldraich et al ., 2014). Here, we showed that arsenic exposure significantly down-regulated the expression of miR-423 in rat liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these roles, miR-26a is also generally thought to be a tumor suppressor (Chen et al ., 2011; Reuland et al ., 2012; Salvatori et al ., 2012; Yang et al ., 2013). The expression of circulating miR-423 is related to myocardial function (Goldraich et al ., 2014). Here, we showed that arsenic exposure significantly down-regulated the expression of miR-423 in rat liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A miR-score, based on cumulative levels of four miRs (including miR-423-5p), was able to discriminate HF patients and controls with an overall accuracy of 90% [42]. We have recently demonstrated a significant difference in miR-423-5p transcoronary gradient in HF outpatients compared with controls [11]. In the present study, we found a higher expression of miR-423-5p in HF patients, with no significant influence of obesity, reinforcing the concept that this particular miR is a reliable biomarker of HF.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…Our group has previously demonstrated that levels of miR-423-5p are elevated in the coronary sinus of HF patients, suggesting that it has a A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 cardiac origin [11]. Other miRs, such as miR-21 and miR-221, have also been implicated in ventricular hypertrophy and HF pathogenesis [12,13].…”
Section: Introductionmentioning
confidence: 96%
“…Thus, this evidence links the known neovascularization defects of diabetes mellitus to cardiac cells by means of miR-bearing exosomes. Another recent study of miRbased trans-coronary biomarkers identified miR-423-5p as a cardiacspecific heart failure plasma marker, positively correlating with the btype natriuretic peptide [185]. Interestingly, miR-423-5p has also been reported, in combination with miR-499, as a putative biomarker discriminating congestive heart failure from AMI [186].…”
Section: Circ-mirs: Biomarkers And/or Effectors In the Context Of Carmentioning
confidence: 94%